Answer:
1. 3(x+4)=3x+11: No solutions.
2. -2(x+3)=-2x-6: Infinite solutions, any number can make the statement true.
3. 4(x-1) = 1/2(x-8): x= 0.
4. 3x-7=4+6 +4x: x= -17.
Explanation:
Equation 1.
1. Write the expression.
![3(x+4)=3x+11](https://img.qammunity.org/2023/formulas/mathematics/college/p1wgc4ylrcbsj4k18wdp0jajjwbuf8me29.png)
2. Simplify the left side of the equation by applying the associative property of multiplication.
This is the rule we're applying:
.
![(3)(x)+(3)(4)=3x+11\\ \\3x+12=3x+11](https://img.qammunity.org/2023/formulas/mathematics/college/u9yaieqrizx1ry62n0h97s62buyfooj8w4.png)
3. Substract 3x from both sides.
![3x+12-3x=3x+11-3x\\ \\12=11](https://img.qammunity.org/2023/formulas/mathematics/college/dka1qtq9urm8kcu7yrebcltj9b42spp1wb.png)
4. Conclude.
As you may notice, we just obtained a false statement in subtitle 3, because 12 doesn't equal 11. Hence, this equation doesn't have solutions.
-------------------------------------------------------------------------------------------------------
Equation 2.
1. Write the expression.
![-2(x+3)=-2x-6](https://img.qammunity.org/2023/formulas/mathematics/college/gw0xr3cnfxt6pwv2qhlhkrgltjwayko7p4.png)
2. Simplify the left side of the equation by applying the associative property of multiplication.
![(-2)(x)+(-2)(3)=-2x-6\\ \\-2x-6=-2x-6](https://img.qammunity.org/2023/formulas/mathematics/college/rc6tfl258nevzm2nv58hyrn8d1pli2mp59.png)
3. Conclude.
Whenever we get an equation that has the same arguments on both sides, this means that there are infinite solutions to this equation, any value of x will make the equation true. Hence, the equation has infinite solutions.
-------------------------------------------------------------------------------------------------------
Equation 3.
1. Write the expression.
![4(x-1) = 1/2(x-8)](https://img.qammunity.org/2023/formulas/mathematics/college/5m98rbufaxn606fy4j81znhi8ctxvvlqri.png)
2. Simplify the both sides of the equation by applying the associative property of multiplication.
![(4)(x)+(4)(-1) = ((1)/(2) )(x)+((1)/(2) )(-8)\\ \\4x-4=(1)/(2) x-4](https://img.qammunity.org/2023/formulas/mathematics/college/2qfosj27vl0gzbekr0n1iszco46vsxr9c8.png)
3. Add 4 to both sides.
![4x-4+4=(1)/(2) x-4+4\\ \\4x=(1)/(2) x](https://img.qammunity.org/2023/formulas/mathematics/college/gwzik3b225lh23f212kbtgs261ruqgmbo9.png)
4. Substract
from both sides.
![4x-(1)/(2) x=(1)/(2) x-(1)/(2) x\\ \\4x-(1)/(2) x=0\\ \\4x-0.5x=0\\ \\3.5x=0\\ \\x=(0)/(3.5 ) \\ \\x=0](https://img.qammunity.org/2023/formulas/mathematics/college/w8nek5eduenbz2od07y25j4ql37swfhaw2.png)
5. Concluide.
The solution for this equation is x= 0.
-------------------------------------------------------------------------------------------------------
Equation 4.
1. Write the expression.
![3x-7=4+6 +4x](https://img.qammunity.org/2023/formulas/mathematics/college/zjawpgodfhveg6s6m3kygkfwa39qmrylk6.png)
2. Simplify by completing the addition.
![3x-7=10 +4x](https://img.qammunity.org/2023/formulas/mathematics/college/nzc67yon68mo0zuqmmns333th51ed18eoc.png)
3. Add 7 to both sides.
![3x-7+7=10 +4x+7\\ \\3x=17+4x](https://img.qammunity.org/2023/formulas/mathematics/college/di4ruyr4snr8jj4am8xbs04rvgloekcx7l.png)
4. Substract 4x from both sides.
![3x-4x=17+4x-4x\\ \\-x=17](https://img.qammunity.org/2023/formulas/mathematics/college/xai75bfcpoa5rqrk5avc2fdlgd98qvmc1r.png)
5. Multiply bith sides by -1.
![(-1)(-x)=(17)(-1)\\ \\x=-17](https://img.qammunity.org/2023/formulas/mathematics/college/ewanvdsi9efuumlfunsflyz5k3vbwqb0fa.png)
6. Conclude.
The solution of this equation is x= -17.